PENGARUH TUNJANGAN KINERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI PRESTASI KERJA PADA PT. PEGADAIAN AREA MAKASSAR 2 - Irmawati; Mashur Razak, Muspa (STKIP Subang, 2025)
This study aims to analyze the effect of Work Allowances and Work Motivation on Employee Performance, as well as the mediating role of Work Achievement in the relationship. Data were analyzed using path analysis techniques on the test results which showed a significant influence between variables. The results of the study revealed that Work Allowances and Work Motivation have a positive and significant direct effect on Employee Performance. Furthermore, these two antecedent variables also have a positive and significant effect on employee Work Achievement. Key findings indicate that Work Achievement significantly mediates the effect of Work Allowances and Work Motivation on Employee Performance. This implies that part of the impact of Work Allowances and Work Motivation on Employee Performance is channeled through increasing individual Work Achievement. This study concludes that efforts to improve work allowances and employee motivation will have a positive impact on performance, both directly and indirectly through increasing work performance.